(untitled) (International Current Pharmaceutical Journal, 2014)
Retinopathy of prematurity (ROP) is known as an abnormal development of the blood capillaries from the eyes retina, and it is met to those infants that were born too early (premature) as its name suggests. Bevacizumab or Avastin belongs to the class of monoclonal antibodies and it is a possible treatment for those patients who have been diagnosed with a recurrent malignant glioma or other cancers due to its behavior to bind selectively to vascular endothelial growth factor (VEGF). In this study, eye drops based on a polyurethane carrier used for bevacizumab were obtained and the degradation of this carrier was studied for three weeks in two different media: simulated body fluid (SBF) and phosphate buffered saline (PBS); the influence of ultrasounds on the degradation of polyurethane carrier was also evaluated. The obtained results suggest that the polyurethane carrier presents a very slow degradation which is beneficial for drugs which require low release rates and on the other hand, the concentrations of the degradation products remain at a low level. DOI: http://dx.doi.org/10.3329/icpj.v3i6.18759 International Current Pharmaceutical Journal, May 2014, 3(6): 275-279